Desain Media Pembelajaran Interaktif Ispring Suite Berbasis Android - Edlino, Yoga; Hamdani, Hamdani (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
This research is conducted to design an Ispring Suite-based interactive learning media on Android for the introduction of electric motors and determine the response of students to the Ispring Suite-based interactive learning media on the topic of electric motor introduction. This study uses a development research (Research and Development) type and employs the 4-D model. The research utilizes a questionnaire as an instrument, consisting of questionnaires for media expert validation, material expert validation, and student response. In this study, an instrument test is conducted to determine the questions' validity, reliability, difficulty level, and discrimination power. The research produces a product in the form of an Android application on the subject of introducing electric motors in the electrical motor installation subject. Based on the data analysis and discussion, the validation testing of the Ispring Suite-based interactive learning media on the topic of electric motor introduction is obtained through three validators in the form of validation questionnaires, namely 2 validators from material experts and 1 validator from a media expert. The assessment by these three validators yielded results indicating that the Ispring Suite-based interactive learning media is considered valid. The validation percentage from the media expert is 86.6% with a valid category. Meanwhile, the average validation percentage obtained from the two material experts is 88.6% with a valid category. Thus, the Ispring Suite-based interactive learning media in the subject of electric motor installation in vocational high school class XI can be considered appropriate and can be used for a broader scope.